GÁBOR KASSAY - IN MEMORIAM - RIGÓ, Petra Renáta; SZENKOVITS, Ferenc (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
The scientific activity of Professor Gábor Kassay (1956-2021), one of the most prolific mathematician in Cluj-Napoca (Romania) is presented, through the memories of some co-authors, with whom he collaborated throughout the four decades of his scientific activity. Mathematics Subject Classification (2010): 01A85, 90C33, 90C47, 46N10. Received 13 August 2021; Accepted 11 October 2021. Published Online: 2022-03-10